Development of a New Ankle Joint Hybrid Assistive Limb - Shigeki Kubota; Hideki Kadone; Yukiyo Shimizu; Masao Koda; Hiroshi Noguchi; Hiroshi Takahashi; Hiroki Watanabe; Yasushi Hada; Yoshiyuki Sankai; Masashi Yamazaki (Medicina, 2022)
Foot and ankle disabilities (foot drop) due to common peroneal nerve palsy and stroke negatively affect patients’ ambulation and activities of daily living. We developed a novel robotics ankle hybrid assistive limb (HAL) for patients with foot drop due to common peroneal nerve palsy or stroke. The ankle HAL is a wearable exoskeleton-type robot that is used to train plantar and dorsiflexion and for voluntary assistive training of the ankle joint of patients with palsy using an actuator, which is placed on the lateral side of the ankle joint and detects bioelectrical signals from the tibialis anterior (TA) and gastrocnemius muscles. Voluntary ankle dorsiflexion training using the new ankle HAL was implemented in a patient with foot drop due to peroneal nerve palsy after lumbar surgery. The time required for ankle HAL training (from wearing to the end of training) was approximately 30 min per session. The muscle activities of the TA on the right were lower than those on the left before and after ankle HAL training. The electromyographic wave of muscle activities of the TA on the right was slightly clearer than that before ankle HAL training in the resting position immediately after ankle dorsiflexion. Voluntary ankle dorsiflexion training using the novel robotics ankle HAL was safe and had no adverse effect in a patient with foot drop due to peroneal nerve palsy.